2021
DOI: 10.1016/j.heliyon.2021.e07046
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 2 (GLP-2) in bovine colostrum and transition milk

Abstract: Bovine colostrum contains growth factors, cytokines, hormones, and enzymes, which have important roles in stimulating gastrointestinal development of neonatal calves. In the present study, we measured the concentration of glucagon-like peptide 2 (GLP-2), one of the gut-derived peptides secreted from intestinal L-cells, in colostrum and transition milk of Japanese black cattle. All colostrum samples were collected within 24 h after calving (d 0) and transition milk was collected at 24, 48 and 72 h relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, concentrations of acylated ghrelin in colostrum were significantly higher than those in maternal plasma, which has been noted for other colostrum hormones, such as IGF-1 and insulin [ 8 , 39 ]. Higher concentrations of hormones in colostrum are not unusual because we have previously reported that concentrations of glucagon-like peptide 2, a gastrointestinal hormone, was also higher in colostrum than in maternal plasma of Japanese Black cattle [ 40 ]. In this study, concentrations of GH, IGF-1, and insulin in milk decreased with time after parturition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concentrations of acylated ghrelin in colostrum were significantly higher than those in maternal plasma, which has been noted for other colostrum hormones, such as IGF-1 and insulin [ 8 , 39 ]. Higher concentrations of hormones in colostrum are not unusual because we have previously reported that concentrations of glucagon-like peptide 2, a gastrointestinal hormone, was also higher in colostrum than in maternal plasma of Japanese Black cattle [ 40 ]. In this study, concentrations of GH, IGF-1, and insulin in milk decreased with time after parturition.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of IgG were 109.88 ± 3.04, 111.68 ± 2.15, and 110.63 ± 1.57 at homogenization levels of 10.34, 13.79, and 17.24 MPa, respectively [ 38 ]. Inabu et al [ 49 ] measured glucagon-like peptide 2 (GLP-2) in bovine colostrum and mature milk by employing solid-phase competition immunoassay. GLP-2 is one of the gut-derived peptides cosecreted with GLP-1 from intestinal L cells in response to nutrient absorption.…”
Section: Impact Of Processing Techniques and Conditions On Colostrum ...mentioning
confidence: 99%